Nanocomplex‐Mediated In Vivo Programming to Chimeric Antigen Receptor‐M1 Macrophages for Cancer Therapy. Issue 43 (12th September 2021) - Kang, Mikyung; Lee, Seong Ho; Kwon, Miji; Byun, Junho; Kim, Dongyoon; Kim, Cheesue; Koo, Sagang; Kwon, Sung Pil; Moon, Sangjun; Jung, Mungyo; Hong, Jihye; Go, Seokhyeong; et al.
Abstract: Chimeric antigen receptor‐T (CAR‐T) cell immunotherapy has shown impressive clinical outcomes for hematologic malignancies. However, its broader applications are challenged due to its complex ex vivo cell‐manufacturing procedures and low therapeutic efficacy against solid tumors. The limited therapeutic effects are partially due to limited CAR‐T cell infiltration to solid tumors and inactivation of CAR‐T cells by the immunosuppressive tumor microenvironment. Here, a facile approach is presented to in vivo program macrophages, which can intrinsically penetrate solid tumors, into CAR‐M1 macrophages displaying enhanced cancer‐directed phagocytosis and anti‐tumor activity. In vivo injected nanocomplexes of macrophage‐targeting nanocarriers and CAR‐interferon‐γ‐encoding plasmid DNA induce CAR‐M1 macrophages that are capable of CAR‐mediated cancer phagocytosis, anti‐tumor immunomodulation, and inhibition of solid tumor growth. Together, this study describes an off‐the‐shelf CAR‐macrophage therapy that is effective for solid tumors and avoids the complex and costly processes of ex vivo CAR‐cell manufacturing. Abstract : Chimeric antigen receptor (CAR)‐T cell therapy is costly and challenged for solid tumor treatment. An approach is presented toward in vivo programming of macrophages into CAR‐M1 macrophages to overcome the challenges. In vivo injection of nanocomplexes of macrophage‐targeting nanocarrier and CAR‐M1 macrophage‐inducing DNA generate CAR‐M1 macrophages that facilitate CAR‐mediated cancer phagocytosis, anti‐tumor immunomodulation, and inhibition of solid tumor growth.